iAMCTD: Improved Adaptive Mobility of Courier Nodes in Threshold-Optimized DBR Protocol for Underwater Wireless Sensor Networks - N. Javaid; M. R. Jafri; Z. A. Khan; U. Qasim; T. A. Alghamdi; M. Ali (International Journal of Distributed Sensor Networks)
We propose forwarding-function ( F F ) based routing protocol for underwater sensor networks (UWSNs): improved adaptive mobility of courier nodes in threshold-optimized depth-based-routing (iAMCTD). Unlike existing depth-based acoustic protocols, the proposed protocol exploits network density for time-critical applications. In order to tackle flooding, path loss, and propagation latency, we calculate optimal holding time ( H T ) and use routing metrics: localization-free signal-to-noise ratio (LSNR), signal quality index (SQI), energy cost function (ECF), and depth-dependent function (DDF). Our proposal provides on-demand routing by formulating hard threshold ( H th ), soft threshold ( S th ), and prime energy limit ( R prime ). Simulation results verify effectiveness and efficiency of the proposed iAMCTD.